Development of LKPD Based on Mangrove Ecosystem to Improve Ecotourism Literacy of Junior High School Students on The South Coast of Lombok Island - Paspania, Karima; Syukur, Abdul; Zulkifli, Lalu (Jurnal Ilmiah Profesi Pendidikan, 2025)
Student Worksheets (LKPD) are teaching materials designed to assist students in the learning process. The design and content structure of the LKPD reflect basic competencies, learning objectives, and indicators. This study aims to determine the characteristics, validity, practicality, and effectiveness of LKPD based on the mangrove ecosystem. The research method follows the 4D model, which consists of the stages of define, design, development, and disseminate. The research design employs a pretest-posttest control group design. Validation and reliability data are based on validation results and the percentage of agreement (PA) values of the research tools, as assessed by three validators, achieving an average score categorized as valid and reliable. Practicality was measured using teacher response questionnaires, which scored an average of 98%, categorized as very practical, and student response questionnaires, which scored an average of 97%, also categorized as very practical. The implementation of PBL-based learning activities achieved an average score of 91%, categorized as very practical. The effectiveness of the LKPD was evaluated using the N-gain test. The average pre-test score of junior high school students in the southern coastal area of Lombok Island was 34%, which improved to 87% in the post-test. The average N-gain score was calculated to be 1.3%, indicating a high level of improvement in students' ecotourism literacy.The N-gain test per indicator revealed that the highest increase in students' ecotourism literacy was in the area of knowledge about ecotourism, with an average improvement of 55.8%. Meanwhile, the average improvement in understanding the benefits of ecotourism for the environment and local communities was 50%. The lowest average increase, at 41.7%, was observed in attitudes toward supporting sustainable ecotourism.